An examination of Richard Peasleee’s Nightsongs, Eric Ewazen’s Sonata for trumpet and piano, Antonio Carlos Jobim’s Desafinado, Horace Silver’s Peace, and Bronislaw Kaper’s Green dolphin street - Ward, Philip Keith (Kansas State University, 2008)
This Master's report contains the biographical, harmonic, and style analysis of the five compositions performed on the author's Master's recital that occurred on October 11th, 2007. The analyses included will provide foundational information for thorough study of Richard Peaslee's Nightsongs, Eric Ewazen's Sonata for Trumpet and Piano, Antonio Carlos Jobim's Desafinado, Horace Silver's Peace, and Bronislaw Kaper's Green Dolphin Street.
Keywords: Richard Peaslee Nightsongs; Eric Ewazen Sonata for Trumpet and Piano; Antonio Carlos Jobim Desafinado; Horace Silver Peace; Bronislaw Kaper Green Dolphin Street; Music (0413)